Microcontroller-Based Mechatronic System with Heating and Humidity Sensor for Silkworm Eggs Incubation - Bakhodirjon, Nasirdinov (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Silkworms have been cultivated for centuries for their valuable silk production. To ensure a successful silkworm rearing process, it's crucial to maintain precise environmental conditions during the early stage of incubation. This article explores the development and implementation of a microcontroller-based mechatronic system equipped with heating and humidity sensors for improving silkworm eggs' incubation process.